Hubungan Fikasi Diri Dengan Tingkat Stres Pada Lansia Penderita Hipertensi Di Dusun Asinan Desa Brani Wetan Kecamatan Maron Kabupaten Probolinggo - Sofiatun munawaroh; Shinta Wahyu Sari; Ainul Yaqin Salam (Jurnal Ilmiah Kesehatan Mandira Cendikia, 2023)
Self efficacynamely the ability of a person to movethoughtand the heart in acting to achieve expectations, in addition to social support factors and psychological aspects, this also affects a person's self-confidence. This research method uses a correlational analytic design with a cross sectional approach. With a population of 58 elderly people with hypertension and a sample of 50 elderly people with hypertension in Asinan Hamlet, Brani Wetan Village, Maron District, Probolinggo Regency, those who met the inclusion and exclusion criteria were taken by purposive sampling. This research instrument uses the General Self Efficacy Scale (GSES) and Perceived Stress Scale (PSS) questionnaire sheets. From the results of this study, 33 respondents (66.0%) had high self-efficacy and experienced mild stress as many as 32 respondents (64.0%) with a value of 0.001 <0.05. It can be concluded that there is a relationship between self-efficacy and stress levels, that is, it can be concluded that high self-efficacy can cause a decrease in stress levels because high self-efficacy will be able to deal with situations that are full of boredom and situations that are full of anxious conditions so that they are not easy to experience. stress.